The Novel Positive Allosteric Modulator of the GABAB Receptor, KK-92A, Suppresses Alcohol Self-Administration and Cue-Induced Reinstatement of Alcohol Seeking in Rats - Maccioni, Paola; Kaczanowska, Katarzyna; Lawrence, Harshani; Yun, Sang; Bratzu, Jessica; Gessa, Gian Luigi; McDonald, Patricia; Colombo, Giancarlo (Frontiers in Cell and Developmental Biology, 2021)
Positive allosteric modulators (PAMs) of the GABAB receptor (GABAB PAMs) are of interest in the addiction field due to their ability to suppress several behaviors motivated by drugs of abuse. KK-92A is a novel GABAB PAM found to attenuate intravenous self-administration of nicotine and reinstatement of nicotine seeking in rats. This present study was aimed at extending to alcohol the anti-addictive properties of KK-92A. To this end, Sardinian alcohol-preferring rats were trained to lever-respond for oral alcohol (15% v/v) or sucrose (0.7% w/v) under the fixed ratio (FR) 5 (FR5) schedule of reinforcement. Once lever-responding behavior had stabilized, rats were exposed to tests with acutely administered KK-92A under FR5 and progressive ratio schedules of reinforcement and cue-induced reinstatement of previously extinguished alcohol seeking. KK-92A effect on spontaneous locomotor activity was also evaluated. Treatment with 10 and 20 mg/kg KK-92A suppressed lever-responding for alcohol, amount of self-administered alcohol, and breakpoint for alcohol. Treatment with 20 mg/kg KK-92A reduced sucrose self-administration. Combination of per se ineffective doses of KK-92A (2.5 mg/kg) and the GABAB receptor agonist, baclofen (1 mg/kg), reduced alcohol self-administration. Treatment with 5, 10, and 20 mg/kg KK-92A suppressed reinstatement of alcohol seeking. Only treatment with 80 mg/kg KK-92A affected spontaneous locomotor activity. These results demonstrate the ability of KK-92A to inhibit alcohol-motivated behaviors in rodents and confirm that these effects are common to the entire class of GABAB PAMs. The remarkable efficacy of KK-92A is discussed in terms of its ago-allosteric properties.